Temporality “Polaroid”: Childhood and Photography in Desierto Sonoro by Valeria Luiselli - Punte , María José (Letras, 2024)
The novel Lost Children Archive (2019), translated into Spanish as Desierto sonoro (2020), as its title suggests, emphasizes a universe of sounds. However, photographic imagery is interwoven throughout the narrative in various ways. In fact, the photographs taken with a Polaroid camera during the family’s journey are included as accompanying material, serving as testimony that the journey took place. This article focuses on analyzing the function of photography and the photographic elements in the novel through their links to childhood. In a brief reflection, the female narrator, who is also a mother, defines the distance between two life stages that appear to be in opposite spheres: “Adults pose for eternity; children, for the moment” (2020: 92). The different ways these two life stages approach the photographic act highlight contrasting experiences of temporality, a question that this text will explore further.